2010
DOI: 10.1530/rep-09-0454
|View full text |Cite
|
Sign up to set email alerts
|

Transient estrogen exposure from birth affects uterine expression of developmental markers in neonatal gilts with lasting consequences in pregnant adults

Abstract: Disruption of estrogen-sensitive, estrogen receptor (ER)-dependent events during porcine uterine development between birth (postnatal dayZPND 0) and PND 14 affects patterns of uterine morphoregulatory gene expression in the neonate with lasting consequences for reproductive success. Uterine capacity for conceptus support is reduced in pregnant adult gilts exposed to estradiol valerate (EV) for 14 days from birth. Objectives here were to determine effects of EV exposure from birth through PND 13 on neonatal ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Neonatal porcine uterine development is both ESR1 dependent and estrogen sensitive (Bartol et al 1993, Tarleton et al 1999, 2003, Chen et al 2010. Therefore, it was important to determine the extent to which uterine ESR1 expression might be regulated via a lactocrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal porcine uterine development is both ESR1 dependent and estrogen sensitive (Bartol et al 1993, Tarleton et al 1999, 2003, Chen et al 2010. Therefore, it was important to determine the extent to which uterine ESR1 expression might be regulated via a lactocrine mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Between birth and PND 3, the porcine endometrium undergoes an important morphogenetic transition, as glandular epithelium differentiates from luminal epithelium and nascent uterine glands begin to penetrate underlying stroma (Masters et al 2007). These events are both ER dependent and estrogen sensitive (Bartol et al 1993, Tarleton et al 1999, 2003, Chen et al 2010. Data support the idea that factors affecting patterns of porcine uterine ESR1 expression and ER activation during early postnatal life define both the developmental program and trajectory of developing uterine tissues with lasting consequences in adults.…”
Section: Introductionmentioning
confidence: 92%
“…There are no available published data that reported the expression of VEGF in the bitch uterus during pregnancy, although there are some information about the expression of this gene in other species of mammals, including pigs, rodents and human (Douglas et al 2009, Kaczmarek et al 2009, Kalkunte et al 2009, Bolat et al 2010, Chen et al 2010, Souza et al 2010. It was previously clearly demonstrated that the activation of VEGF-related biochemical pathway induces the processes of proper angiogenesis and vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…HOXA10 has been shown to be essential not only for uterine development, but also for implantation [8]. This gene has been shown to be expressed in adult murine [9], canine [10], primate [11], human [8, 9], and more recently porcine [12,13] uteri. In pigs, HOXA10 protein was localized in the luminal and glandular epithelium, stroma and blood vessels of the endometrium, but also in the myometrium of the uterus [13].…”
mentioning
confidence: 99%
“…However, the majority of embryos commence implantation but are resorbed early in the post-implantation period [14]. Moreover, HOXA10 expression is regulated by P4 and/or E2 in human [8] Recently, E2-stimulated expression of HOXA10 gene was observed in uteri of postnatal day 14 piglets [12].Prostaglandins (PGs) produced by the uterus play an essential role in regulation of the estrous cycle and during maternal recognition of pregnancy in many species, including the pig [4,18]. The rate-limiting enzyme in PG production is prostaglandin H synthase (PGHS; also known as cyclooxygenase), which catalyzes the conversion of arachidonic acid to PGH2 [19], the common substrate for various PGs.…”
mentioning
confidence: 99%